Interleukin 28B Gene Polymorphism and Association with Chronic Hepatitis C Therapy Results in Latvia. (24th April 2012) - Tolmane, Ieva; Rozentale, Baiba; Keiss, Jazeps; Ivancenko, Ludmila; Subnikova, Nadezda; Reinholde, Zaiga; Kozlovska, Ieva; Sumlaninova, Nina; Laivacuma, Sniedze; Simanis, Raimonds
Abstract : Introduction . With the standard treatment of chronic hepatitis C, sustained virological response (SVR) can be achieved only in half of all patients. Interleukin-28B appears to be involved in the control of HCV infection, and the genetic polymorphism of the encoding IL-28B gene may determine the efficacy of clearance of HCV. The aim of this paper was to detect IL-28B gene polymorphism in Latvia and to analyze therapy results. This is the first study on IL-28B gene polymorphism in Latvia. Material and Methods . There were 159 chronic viral hepatitis C patients included in the study. In order to detect IL-28B gene polymorphism, we used molecular biology techniques and methods: classical DNA separation, amplification by PCR, and standard sequencing. Genotype was defined as CC, CT, TC, or TT type. 142 patients were treated with the standard of care treatment. Results were analyzed according to IL-28B polymorphism. Results . There were 53 patients (33%) with CC genotype, 84 patients (53%) with CT/TC genotype, and 22 patients (14%) with TT genotype. 34 patients (74%) in CC genotype subgroup achieved SVR versus 50 patients (52%) in non-CC subgroups. In patients with genotype 1, SVR was achieved in 16 patients (84%) in CC subgroup versus 30 patients (47.6%) in non-CC subgroups, P = 0.007 . Conclusions . The most common genotype of IL28B in Latvia is CT/TC, with an incidence of 53%. Patients with CC genotype achieved SVR more often than CT or TT subgroups. IL28B gene polymorphism therefore is a strong predictor of treatment result.